2023
DOI: 10.1021/acs.cgd.2c00724
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Polymorphic Transitions in n-Type Organic Semiconductor Single Crystals by Alkyl Chain Engineering

Abstract: Control of polymorphic behavior is crucial for designing functional organic semiconductor devices as even a slight structural difference may translate to dramatically different electronic properties. One route to controlling structure is through stimulus-induced polymorph transitions, which allows for switching those electronic properties. However, despite advances in predicting crystal structures, the molecular design characteristics governing the polymorphic transition mechanism remains unknown. Here, we sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Previous work showed that two-dimensional quinoidal terthiophene (2DQTT- o -B) (Figure a) exhibits a rich set of polymorph phase transitions with drastically different electronic properties. ,, Powders and films typically form a metastable polymorph I′ initially (depending on solvent and drying process), which are annealed to the stable polymorph I (Figure b). Additionally, the hysteresis for the II–III transition is substantial at 78 °C, suggesting a large energy barrier for the polymorph transition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work showed that two-dimensional quinoidal terthiophene (2DQTT- o -B) (Figure a) exhibits a rich set of polymorph phase transitions with drastically different electronic properties. ,, Powders and films typically form a metastable polymorph I′ initially (depending on solvent and drying process), which are annealed to the stable polymorph I (Figure b). Additionally, the hysteresis for the II–III transition is substantial at 78 °C, suggesting a large energy barrier for the polymorph transition.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the close proximity of the II–III polymorph transition temperature with the melting point for 2DQTT- o -B, accessing the I–III–IV transition with laser pulses becomes difficult. However, the polymorph transition behavior in 2DQTT is highly tunable via changing the length of the alkyl side chains . Shortening the alkyl chains increases the transition temperature to obtain polymorph III as well as increases the melting point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our focus is on achieving high electrical conductivity through either the continuous coordination bonds formed between metal centers and ligands or via noncovalent interactions such as the π–π stacking interaction between organic moieties possessing π-conjugation. Notably, organic semiconductors offer numerous advantages over conventional inorganic counterparts, including lightweightness, flexibility, and the ease of depositing thin films over large surfaces. Traditionally, the structure–function co-relationships of organic semiconductors have been investigated through chemical modifications of organic molecules. , However, polymorphism offers an ideal platform for such investigations by excluding the influence of chemical modification. Consequently, substantial progress has been made in understanding the impact of polymorphism on semiconducting properties using crystalline materials made of conjugated small molecules. It has also been observed that slight changes in the crystal packing significantly affect charge transport in electronic devices. N -salicylideneanilines, derived from Schiff base condensation reactions between salicylaldehyde and aniline derivatives, deserve special mention in this context.…”
Section: Introductionmentioning
confidence: 99%